Post‐2015 Global Governance of Official Development Finance: Harnessing the Renaissance of Public Entrepreneurship. (August 2015) - Xu, Jiajun; Carey, Richard; Gore, Charles
Abstract The spirit of 'public entrepreneurship', reignited by large‐scale and long‐term official finance from emerging economies, is now driving a process of 'creative destruction' in the established systems for governing official development finance primarily forged among advanced economies. In response to this burgeoning official finance from emerging economies once on the margins or outside of these established systems, potentially seismic shifts are occurring in three central governance systems—the reporting systems for official development assistance in the OECD Development Assistance Committee, OECD export credit disciplines and debt sustainability in the Bretton Woods Institutions. Emerging economies create competitive pressures that work to redress the undue rigidities in these established frameworks, opening the way to meeting vast development financing needs. If not well managed or coordinated, however, growing official finance runs the risk of further rounds of financial arms races and debt crises. To harness the processes of 'public entrepreneurship' as a force for good in realizing a transformative post‐2015 development agenda requires international cooperation to reshape global governance of official development finance. Copyright © 2015 John Wiley & Sons, Ltd.